Antimicrobial resistance profiles of bacteria associated with lower respiratory tract infections in cats and dogs in England. (11th August 2021) - Mavrides, Daphne E.; Morgan, Alice L.; Na, Jea G.; Graham, Peter A.; McHugh, Timothy D.
Abstract: Background: Bacterial lower respiratory tract infections (bLRTIs) are common and potentially life threatening in cats and dogs. Antibiotic treatment is often initiated before the diagnosis of bLRTI; therefore improved knowledge of the aetiology and antibiotic susceptibility patterns of these infections is essential to inform empiric antibiotic choices. Methods: A retrospective study of microbiological, cytological results and their drug susceptibilities from lower respiratory samples ( n = 1989) processed in a UK commercial laboratory between 2002 and 2012 was carried out. Results: Thirty‐nine per cent of feline samples and 50% of canine samples were positive for bacterial growth with most yielding a single organism (72 % and 69%, respectively). Bordetella bronchiseptica (20.2% from dogs and 2.3% from cats), Pasteurella spp. (23.2%, 31.8%), E. coli (16.2%, 13.6%) and Pseudomonas spp. (11.1%, 11.4%) were most frequently isolated from cytologically positive samples which contained intracellular bacteria (10%, 14%). Amoxycillin‐clavulanate, cephalothin, cefovecin, oxytetracycline and trimethoprim/sulfamethoxazole showed modest in vitro activity against E. coli from dogs (approximately 70% susceptibility). Pseudomonas spp. were resistant to enrofloxacin (50%), ticarcillin (25%) and marbofloxacin (13%) but showed lower or zero resistance to aminoglycosides (approximately 7%) and ciprofloxacin (0%). Multi drug resistance (acquired resistance to three or more antimicrobial drug classes) was particularly common among E. coli isolates, with 23% from feline samples and 43% from canine samples. Conclusion: Resistance to certain first‐choice antibiotics was detected in bLRTIs highlighting the need for continued monitoring and sound evidence to inform decision‐making in the management of these infections.